No mention kinship. Louis XIV and the Great Habsbourg - Édouard, Sylvène (Cuadernos de Historia Moderna, 2014)
The aim of this paper is to show the place of Austrias mayores in Louis XIV’s education and discourse of greatness, who was their direct descendant by his mother Ana of Austria, and linked with those of Vienna by his grandmother Marie de Medici, grand-daughter of Emperor Ferdinand Ist. In this time of hegemony’s changeover, the apologists of the King of France, mostly academicians, experienced difficulties in naming this relationship to serve the glory of their master : Charles V and Philip II had been the dominant figures of the last century without their glory reflected upon their descendant. If Louis XIV was not presented as their heir, at least he has been raised in the knowledge of their exemplaries figures to eventually capture their Imperial’s imaginery.